Application of advanced oxidation methods for landfill leachate treatment – A review. Issue 6 (1st November 2003) - Wang, F; Smith, Daniel W; El-Din, M Gamal
Abstract : Landfill leachate is a complex wastewater generated when the moisture content or the water content of the landfilled solid waste is larger than its field capacity. The major fraction of old or biologically treated landfill leachate is large recalcitrant organic molecules that are not easily removed during biological treatment. Advanced oxidation using ozone (O3 ), ozone with hydrogen peroxide (O3 /H2 O2 ), ozone with ultraviolet light (O3 /UV), hydrogen peroxide with ultraviolet light (H2 O2 /UV), Fenton process (H2 O2 /Fe 2+ ), and photo-Fenton process (H2 O2 /Fe 2+ /UV) for the treatment of old or biologically treated landfill leachate has been intensively studied in the past decade to improve the removal of these large recalcitrant organic molecules or to transform them into more easily biodegradable substances. The characteristics of landfill leachate and the mechanisms of O3, O3 /H2 O2, O3 /UV, H2 O2 /UV, H2 O2 /Fe 2+, and H2 O2 /Fe 2+ /UV oxidation processes and their applications for landfill leachate treatment are reviewed in this paper. In addition, the influences of ammonia nitrogen (NH3 -N), pH, and alkalinity on the advanced oxidation processes applied for treating landfill leachates as well as the methods for the removal of the oxidants residues are also discussed in this paper. Key words : landfill leachate, ozone, hydrogen peroxide, UV, Fenton processes, photo-Fenton processes, refractory organics.